2020
DOI: 10.1039/d0qi00084a
|View full text |Cite
|
Sign up to set email alerts
|

GdF3hollow spheres: self-assembly and multiple emission spanning the UV to NIR regions under 980 nm excitation

Abstract: Monodispersed GdF3:Er3+,Yb3+ hollow submicrometer spheres were successfully synthesized by self-assembly of ∼16 nm nanocrystals, and exhibit unique strong emissions spanning from UV to NIR under excitation at 980 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[34] Similarly, in Yb 3+ /Er 3+ /Gd 3+ triply-doped systems, Er 3+ ions also can transfer energy to Gd 3+ ions for UV emission by 980 nm excitation. [35] To realize an efficient UV emission process through multiphoton upconversion, selecting appropriate host materials is essential. [24a,36] For example, Capobianco and co-workers reported that LiYF 4 -based UCNPs were preferable to the NaYF 4based counterparts in some cases, especially for UV-blue upconversion emission.…”
Section: Uv Emission By 980 Nm Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Similarly, in Yb 3+ /Er 3+ /Gd 3+ triply-doped systems, Er 3+ ions also can transfer energy to Gd 3+ ions for UV emission by 980 nm excitation. [35] To realize an efficient UV emission process through multiphoton upconversion, selecting appropriate host materials is essential. [24a,36] For example, Capobianco and co-workers reported that LiYF 4 -based UCNPs were preferable to the NaYF 4based counterparts in some cases, especially for UV-blue upconversion emission.…”
Section: Uv Emission By 980 Nm Excitationmentioning
confidence: 99%
“…[ 34 ] Similarly, in Yb 3+ /Er 3+ /Gd 3+ triply‐doped systems, Er 3+ ions also can transfer energy to Gd 3+ ions for UV emission by 980 nm excitation. [ 35 ]…”
Section: Strategies For Nir‐to‐uv Upconversionmentioning
confidence: 99%
“…Hollow inorganic nanoparticles featuring a cavity space are one of the most attractive functional nanomaterials 31 , 32 . Hollow structure UCNPs have the properties of large internal surface area and high surface permeability, and theoretically have high light collection efficiency that is conducive to obtaining excellent luminescence properties and thus beneficial to temperature sensing 33 , 34 . However, the controllable design, structural engineering, and fine-tuning of nanoparticles to construct special structural materials with desirable size, composition, morphology, and physicochemical properties are not an easy task 35 37 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the brightness and quantum yield of UCNPs are substantially weak, partially owing to the relatively low doping concentrations of the sensitizer (<20 mol%) and activator (<2 mol%). [13][14][15] NaYbF 4 nanoparticles have been proposed as a promising alternative host to canonical NaYF 4 for enhancing the brightness and efficiency of UCNPs, as they possess the highest content of Yb 3+ , and are expected to amplify the absorption cross section for maximizing the use of incident light and accelerate energy transfer to the activator. [16][17][18] Thus, core-shell nanostructures with NaYbF 4 as an intermediate shell have been used to not only boost upconversion intensity, but also tailor the emission profile to enhance multiphoton emission.…”
Section: Introductionmentioning
confidence: 99%